Integrating Articulate Storyline into Problem-Based Learning to Enhance Students’ Conceptual Understanding - Saputri, Mawarni; Musdar, Musdar; Rizvia, Fuddhah; Nurulwati, Nurulwati; Susanna, Susanna; Nithieahvathiy, Nithieahvathiy (Jurnal Pendidikan MIPA, 2025)
Low conceptual understanding in physics remains a recurring problem in secondary education, particularly because learning is often dominated by conventional methods. Although the Problem-Based Learning (PBL) model can promote critical thinking, its potential is not maximized without the support of interactive media. This study aims to determine the effectiveness of integrating Articulate Storyline into PBL as a strategy to enhance students’ conceptual understanding of physics. This quasi-experimental research employed a non–equivalent control group pretest–posttest design, involving 50 tenth-grade students at SMAN 1 Labuhan Haji Barat, South Aceh, Indonesia. Class X IPA 1 (25 students) served as the experimental group, while Class X IPA 2 (25 students) acted as the control group, which was selected by the purposive sampling technique. Instruments consisted of a two-tier concept test and a student response questionnaire. Data were analyzed using N-Gain, an independent t-test, and qualitative categorization of conceptual understanding. The results showed that the experimental group achieved a higher N-Gain of 0.52, categorized as medium, compared to the control group of 0.26, which was categorized as low. An independent t-test revealed a significant difference between the two classes with an alpha value of 0.05. Qualitative analysis revealed a significant shift in students’ conceptual categories, as the number of students in the “not understanding” and “misconception” groups decreased. In contrast, those in the “understanding concept” category increased substantially. Moreover, 91.2% of students responded positively to the use of Articulate Storyline, particularly appreciating its visual simulations, structured learning flow, and interactive quizzes. Integrating Articulate Storyline into PBL effectively enhances students’ conceptual understanding and engagement in physics. This synergy provides empirical evidence that technology-enhanced PBL not only improves learning outcomes but also reduces misconceptions and fosters more meaningful learning experiences.    Keywords: articulate storyline, conceptual understanding, problem-based learning.